Pelatihan Akuntansi bagi UMKM Food and Beverages di Kota Pekanbaru - Munir, Alchudri; Darnilawati; Riansyah, Rhonny; Hasanah, Nur (Jurnal Pengabdian Masyarakat Isei, 2023)
In developing MSME businesses that are more advanced and able to survive economic shocks and provide opportunities for the world of work, financial strength is needed to run MSME businesses. Financial reports are very important in the development of MSME businesses, especially in increasing potential and innovation in competition among MSMEs. The importance of financial reports for MSMEs in efforts to increase financial capabilities so that they are able to compete, develop and move up in class. The results of the activity stated that the accounting training participants were very enthusiastic in increasing their knowledge and understanding of accounting records and were motivated to implement recording of the financial reports of the businesses they run. So, through accounting training, it is hoped that MSMEs can develop and increase income, and they are also expected to be able to make neat and correctly recorded financial reports. The method used is through providing accounting training, direct practice or simulation of accounting records that are correct and easy to understand as well as open discussions.